A cell line resource derived from honey bee (Apis mellifera) embryonic tissues. - Michael J Goblirsch (Public Library of Science (PLoS), 2013)
A major hindrance to the study of honey bee pathogens or the effects of pesticides and nutritional deficiencies is the lack of controlled in vitro culture systems comprised of honey bee cells. Such systems are important to determine the impact of these stress factors on the developmental and cell biology of honey bees. We have developed a method incorporating established insect cell culture techniques that supports sustained growth of honey bee cells in vitro. We used honey bee eggs mid to late in their embryogenesis to establish primary cultures, as these eggs contain cells that are progressively dividing. Primary cultures were initiated in modified Leibovitz's L15 medium and incubated at 32(°)C. Serial transfer of material from several primary cultures was maintained and has led to the isolation of young cell lines. A cell line (AmE-711) has been established that is composed mainly of fibroblast-type cells that form an adherent monolayer. Most cells in the line are diploid (2n = 32) and have the Apis mellifera karyotype as revealed by Giemsa stain. The partial sequence for the mitochondrial-encoded cytochrome c oxidase subunit I (Cox 1) gene in the cell line is identical to those from honey bee tissues and a consensus sequence for A. mellifera. The population doubling time is approximately 4 days. Importantly, the cell line is continuously subcultured every 10-14 days when split at a 1:3 ratio and is cryopreserved in liquid nitrogen. The cell culture system we have developed has potential application for studies aimed at honey bee development, genetics, pathogenesis, transgenesis, and toxicology.